A Pilot Assessment on the Role of Procalcitonin Dynamic Monitoring in the Early Diagnosis of Infection Post Cardiac Surgery - Miao, Qiang; Chen, Sheng-nan; Zhang, Hao-jing; Huang, Shan; Zhang, Jun-long; Cai, Bei; Niu, Qian (Frontiers in Cardiovascular Medicine, 2022)
Purpose: To evaluate the value of dynamic monitoring of procalcitonin (PCT) as a biomarker for the early diagnosis of postoperative infections in patients undergoing cardiac surgery. Methods： 252 patients who underwent cardiac surgery were retrospectively included. The postoperative patients' PCT level, change value (△PCT) and clearance rate (△PCTc) were compared between the infected and noninfected groups in adult and pediatric patients on postoperative days (POD) 1, 3, and 5. The area under the receiver operating characteristic curve (AUC) was used to evaluate the diagnostic value. Results: PCT concentration decreased progressively in the noninfection group in adult and pediatric patients; PCT concentration continued to rise until it peaked on POD 3 in the infection group. In adult patients, the AUC of PCT for diagnosis of infection on POD 1, 3, and 5 were 0.626, 0.817, and 0.806, with the optimal cut-off values of 7.35 ng/ml, 3.63 ng/ml, and 1.73 ng/ml, respectively. The diagnostic efficiency of △PCT3 and△PCTC3 were significantly better than △PCT5 and △PCTC5, respectively. While in pediatric patients, the AUC of PCT for diagnosis of infection on POD 1, 3, and 5 were 0.677, 0.747, and 0.756, respectively, and the optimal cut-off values were 27.62 ng/ml, 26.15 ng/ml, and 10.20 ng/ml. Conclusion: This study showed that dynamic monitoring of PCT levels could be an effective clinical means to help to discover postoperative infection earlier. The PCT level and its change indicators on POD 3 in adult patients and the PCT level on POD 5 in children can indicate infection.